Carbon-Nanostructures for Tissue Engineering and Cancer Therapy - Hosseini S.A.; Kargozar S.; Kumar A.; Kim H.-W. (My University, 2025)
Carbon nanostructures have enticed significant attention in biomedical areas over the past few decades owing to their unique electrical, physical, and optical features, biocompatibility, and versatile functionalization chemistry. These nanostructures can be categorized into diverse groups based on their morphology, including fullerenes, nanotubes (e.g., single-walled carbon nanotube (SWCNT) and multi-walled carbon nanotube (MWCNT)), nanodiamonds, nanodots, graphite, and graphene derivatives. Emerging biomedical trends indicate the usefulness of carbon nanostructures in gene/drug delivery, cancer theranostics, and tissue engineering and regenerative medicine, either alone or in combination with other biocompatible materials. This chapter presents a comprehensive overview of various types of carbon family nanostructures and their characteristics. We further highlight how these properties are being utilized for various medical applications. © 2024 Bentham Science Publishers.